Comment on "The Effects of Secular Calcium and Magnesium Concentration Changes on the Thermodynamics of Seawater Acid/Base Chemistry: Implications for Eocene and Cretaceous Ocean Carbon Chemistry and Buffering" by Hain et al. (2015). Issue 5 (16th May 2018) - Zeebe, Richard E.; Tyrrell, Toby
Abstract : Hain et al. (2015, https://doi.org/10.1002/2014GB004986, hereafter H15) calculated effects of changing [Ca 2+ ] and [Mg 2+ ] on the equilibrium constants of the CO2 ‐CaCO3 system in seawater based on a Pitzer ionic interaction model. We show here that critical results presented in H15 are fundamentally wrong. We therefore do not recommend using H15's stoichiometric equilibrium constants to correct for past changes in major‐ion seawater composition. Key Points: We show here that critical results presented in H15 are fundamentally wrong We do not recommend using H15's stoichiometric equilibrium constants to correct for past changes in major ion seawater composition